An Evaluation of Effective Factors in Learning Transfer of Nursing On-the-Job Training Courses in Work-Environment Based on Holton's Transfer Model - mehdi mohammadi; reza naseri jahromi; zeinab mokhtari; athar rasekh; Alireza Abedi; Rahil Naseri (Zanjan University of Medical Sciences and Health Services, 2017)
Background of Objective: Nursing is one of the health care jobs. In addition to health care, they need to continue education for individual development and be aware of the latest medical science achievements. The main purpose of this study was an evaluation of effective factors in learning transfer of nursing on the job training courses in work environment based on Holton's transfer model. Materials and Methods: This was a descriptive, cross-sectional study in which the population was all of Jahrom University of Medical Sciences nurses. Passing on-the-job training courses in 2015 was inclusion criterion. Using random sampling method and Cocran formula, 95 nurses were selected. Research instrument was learning transfer system inventory that was distributed after its validity and reliability were calculated. Data was analyzed by inferential statistical methods and SPSS21. Results: The results showed that effective individual, organizational and educational factors in learning transfer of on-the-job training courses in work environment are important. Also, they showed that individual was the most dominant effective factor (P< 0.05). Conclusion: With special attention to the nurse's on- the -job training courses, it is possible to transfer learning to work environment.